Aesthetic spiral for design - Gobithaasan .R.U; Kenjiro T. Miura (Universiti Kebangsaan Malaysia, 2011)
A planar spiral called Generalized Log Aesthetic Curve segment (GLAC) has been proposed using the curve synthesis process with two types of formulation; ρ-shift and κ-shift. Both methods were carried out by extending the formulation of Generalized Cornu Spiral (GCS) in a similar manner to the Log Aesthetic Curve (LAC). The family of GLAC comprises of planar curves of high quality such as GCS, LAC, clothoid, logarithmic spiral and circle involute. The GLAC segment has an additional parameter to determine its shape as compared to GCS and LAC segment, hence an extra constraint can be satisfied when shaping the GLAC segment. The last section of the paper shows a numerical example.